Pritchard Street, 1889. Johannesburg - Unknown (My University, 2011)
Corner of Eloff Street showing on the left, the first Chundleigh's Building site of the present O.K.Bazaars and across the road, the single-storey building on the present Cuthbert's site.
Black and White photograph.